Antara Nama dan Budaya Fonestemik, Onomatope, dan Kearifan Lokal dalam Penamaan Jajanan Tradisional di Jawa Timur – Kajian Antropolinguistik - Filia, Ihza; Zakiyah, Milatuz (Center of Language and Cultural Studies, 2025)
Snacks are specific forms of food that play an important role in people's lives and reflect local beliefs, culture and values. In Javanese society, the naming of traditional snacks is often associated with physical characteristics and sounds, so this research focuses on identifying the forms of naming traditional East Javanese snacks that contain phonestemic and onomatopoeic elements and their relationship with local culture. Furthermore, this study aims to describe the kinds of onomatopoeia, phonestemics and cultural elements to show the various forms underlying the diversity of Javanese language in the naming of traditional East Javanese snacks. The data sources of the research are reliable informants who can provide information about traditional East Javanese snacks, literature, and supporting documents. The research data was taken in December 2024 - February 2025. Data was collected using literature study, interview, and observation techniques. Furthermore, the data that has been classified is then analyzed using agih and padan methods. Using a qualitative descriptive approach, this study analyzed phonemically 55 traditional East Javanese snack names and found phonestemic elements in the form of (1) big and small nuances; (2) hard and soft nuances, as well as onomatopoeic elements consisting of (1) root words as basic words; (2) root words plus formatives; (3) root words doubled; (4) root reduplication; and (5) based on compound words. In addition to the naming of traditional East Javanese snacks being analyzed for its formation, the naming of these snacks is also based on various cultural influences that develop in the community and become local wisdom. The results show that the character of the formation of traditional East Javanese snack names is not only unique from its phonestemic and onomatopoeic naming, but also closely related to local wisdom and cultural identity of the local community.